A mischievous young rogue and a dwarf: Reflections on the role of the panakawan in the Age of Prince Diponegoro (1785-1855) - Peter Carey (The Center for Disability Studies and Services Brawijaya University, 2014)
The late eighteenth and early nineteenth century world in which the young Prince Diponegoro (1785-1855) grew up was a deeply traditional one. In the Yogyakarta court of his grandfather, Sultan Hamengkubuwono II (reigned 1792-1810/1811-12/1826-28), and father, the third sultan (reigned 1812-1814), there were special categories of court servants (abdi-Dalem) who served the ruler and provided his close protection. These included the para Nyai (personal female retainers), in particular the elderly Nyai Keparak, who carried the ruler's betelnut (sirih) box and spittoon (Carey 2008: 366, 403); the prajurit Ã¨stri (pasukan Langenkusumo) or Amazon corps who acted as the personal bodyguards of the ruler and were renowned for their skill on horseback (Carey 2008: 76-77); the polowijo or nonok (royal dwarves, the hydrocephalic and those with other unusual physical deformities) who acted as the court jesters (hansworst) and warders against evil; and the panji or young noblemen who formed part of the ruler's intimate circle much like the bachelor knights of the European medieval courts (Carey 2008: 179-80). Amongst these intimate court servitors none were important than the panakawan. As intimate assistants of the nobility, they combined many roles: tutor, servant, bodyguard, clown, adviser, masseur, herbalist, interpreter of dreams. Their pithy wit deflated pomposity and re-connected the high-born with the world of the Javanese village. As in the wayang clown-servitor figure of the renowned senior panakawan of the Pandawa brothers Semar they might even be gods in disguise. This mix of the demotic and the divine reflects the paradox at the heart of Javanese culture the seemingly misshapen being the vehicle of ultimate wisdom: Een Gedrocht en toch de Volmaakte Mens (a monster but still a perfect man) as the title of a famous study of the Suluk Gathotloco has it (Akkeren 1951).